PENGARUH BUDAYA KERJA, MOTIVSI KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN CV MALALA - Achmad Zulfikri; Miftahul Munir; Anita Sumelvia Dewi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of work culture, work motivation, and work environment on employee performance at CV Malala. The research employed a quantitative method with a saturated sampling technique, involving 30 respondents. Data were analyzed using validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, F-test, and coefficient of determination with SPSS software. The results reveal that work culture and work motivation have no significant effect on employee performance, while the work environment has a significant partial effect. Simultaneously, work culture, work motivation, and work environment significantly affect employee performance, contributing 77.7%, while the remaining 22.3% is influenced by other factors not examined in this study.